The Role of Islamic Economic Law in Increasing Financial Inclusion in the Era of Technology and Globalization - Ilham, Muhammad Ilham; Dimas, Muhammad Dimas (Alhamdulillah : Jurnal Agama Islam, 2023)
This study aims to analyze the role of Islamic economic law in increasing financial inclusion in the era of technology andglobalization. Along with the rapid development of the fintech sector and the adoption of digital technology in thefinancial world, Islamic economic law provides a strong foundation for creating a fair and transparent financialsystem. The results of the study show that there has been a significant increase in the number of Islamic financial institutions, users of Islamic banking services, and Islamic fintech transactions from 2020 to 2023. In addition, public acceptance of Islamic-based digital payments and the use of digital financial applications is increasing, reflecting the increasingly widespread application of Islamic principles in the financial sector. Despite challenges in terms of financial literacy and technology integration, the Islamic financialsector shows great potential in expanding financial access for the community, especially through inclusive Islamicfinancing. Therefore, further efforts are needed to improve Islamic financial literacy, strengthen cooperation betweenfinancial institutions and the technology sector, and ensure policies that support the development of this sector. Thisstudy is expected to provide insight into the development of a more inclusive financial system based on the principles ofsocial justice.